A method of network robustness under strategic goals for project portfolio selection. (November 2021) - Bai, Libiao; Han, Xiao; Wang, Hailing; Zhang, Kaimin; Sun, Yichen
Highlights: A method is proposed to select the robust project portfolio under the strategic goal. Define the Strategic Loss Rate, which is the robustness evaluation index. The project portfolio is selected based on the network method. Abstract: Selecting a rational project portfolio is a key step in achieving the strategic goals of an enterprise. However, the selection is challenging due to complicated relationships in the project portfolio network. This paper proposes a method based on complex network theory to select a robust project portfolio under strategic goals. The proposed method consists of three phases. In the first phase, the strategic goal of the enterprise is divided into several sub-goals, and the approach degrees between projects and sub-goals are determined by the Euclid approach degree. In the second phase, the coupling coordination degree (CCD) of the project portfolio is determined by using the modified CCD model. The optimal project portfolio that considers the robustness of the project portfolio network under random attack is obtained in the last phase. A numerical example demonstrates how the project portfolio selection method fits in an enterprise and proves the model's efficiency via selection results obtained with different attack intensities. This research provides theoretical guidance and practical applied value for theoretical researchers and companies.